2022
DOI: 10.1002/vetr.1317
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study on the in‐herd prevalence ofMycoplasma hyopneumoniaeat different stages of pig production

Abstract: Background: A cross-sectional study was carried out to assess the prevalence of Mycoplasma hyopneumoniae infections before vaccination in 3-week-old piglets and to gain information about infection dynamics. Methods: In 13 German and three Austrian farms with a known history of enzootic pneumonia, 790 piglets and 158 sows were sampled (blood samples, tracheobronchial swabs [TBS] [piglets], laryngeal swabs [LS] [sows]), and 525 pen-based oral fluids (OFs) were collected in growing and fattening pigs. Laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…This highlights the need to develop DIVA compliant vaccines against M. hyopneumoniae [ 31 ]. In this study, gilts were significantly more often infected with M. hyopneumoniae , and gilts had more often M. hyopneumoniae -specific antibodies compared to sows, which is in line with previous findings [ 3 , 10 , 12 , 13 ]. However, in most studies M. hyopneumoniae PCR prevalence or seroprevalence was investigated in breeding animals only to draw conclusions on their offspring [ 5 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This highlights the need to develop DIVA compliant vaccines against M. hyopneumoniae [ 31 ]. In this study, gilts were significantly more often infected with M. hyopneumoniae , and gilts had more often M. hyopneumoniae -specific antibodies compared to sows, which is in line with previous findings [ 3 , 10 , 12 , 13 ]. However, in most studies M. hyopneumoniae PCR prevalence or seroprevalence was investigated in breeding animals only to draw conclusions on their offspring [ 5 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Between the farms the variation of M. hyopneumoniae PCR prevalence was high. Although M. hyopneumoniae circulation was suspected, the PCR prevalence was low or even zero in the breeding animals on some farms [ 13 ]. For the seroprevalence on the other hand, the percentages were high and there was less variation between farms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…study of 10 Flemish breeding herds revealed an M hyopneumoniae detection level between 0 and 43.8 per cent in breeding animals. 20 However, similar to the findings of Deffner and colleagues' study, 17 the gilts sampled in this study were significantly more likely to test positive for M hyopneumoniae DNA than older sows. 20 The difference between the findings of Deffner and colleagues' study and those of previous studies might be explained by the fact that they only sampled clinically healthy pigs.…”
Section: What You Need To Knowsupporting
confidence: 86%